The Influence of E-Learning Systems on Student Learning Outcomes in Event Organizer Course - Yuzia Eka Putri (JURNAL PENDIDIKAN DAN KELUARGA, 2021)
This research is motivated by the low value of students in the event organizer subjects observed since online learning. This study aims to look at the influence of online learning system variables on the learning outcomes of Unimed culinary students. This research was classified as quantitative research. The research population was students in the culinary Studies program, while the sample was food students who completed the event organizer course. The data analysis technique used was descriptive data analysis. The data analysis requirements test consisted of normality and homogeneity tests, and hypothesis testing with the "t" test. Hypothesis test results show that tcount> ttable or 7.24> 166 at a significance level of 5%. It means that there is a significant influence on online learning systems on culinary student learning outcomes in event organizer courses.